Tuning electronic properties in LaNiO3 thin films by B-site Cu-substitution. Issue 36 (27th August 2020) - Sønsteby, Henrik H.; Skaar, Erik; Bratvold, Jon E.; Freeland, John W.; Yanguas-Gil, Angel; Elam, Jeffrey W.; Nilsen, Ola; Fjellvåg, Helmer
Abstract : Cu-Substitution in LaNiO3 by atomic layer deposition provides films spanning six orders of magnitude in resistivity, with metal insulator transition temperatures from 0 K to room temperature. Abstract : Resistors are essential parts of futuristic all-oxide electronic architectures, yet easily overlooked due to their apparent simplicity. Herein, design of thin films with specific resistance spanning six orders of magnitude by partial substitution of Cu 2+ for Ni 3+ in the metallic conductor LaNiO3 is shown. Substitution is attainable across the whole composition range using atomic layer deposition on LaAlO3 (100)pc substrates, however with some inclusion of Ruddlesden–Popper RP1 phase (La2 CuO4 ) at high levels of Cu-incorporation. The thermal stability of the resistance is based on a metal–insulator transition that evolves from non-existent for LaNiO3 to above room-temperature for high Cu 2+ substitution. This provides further insight in the metal–insulator transition found for correlated rare-earth nickelates, especially the type of transition seen for ultrathin films of LaNiO3 that is usually attributed to oxygen vacancy formation. Materials with variable resistivity and metal–insulator-transition temperatures are key in the design of futuristic electronics such as metal–insulator-transition-driven neuromorphic devices.